2008
DOI: 10.1152/ajpcell.00492.2007
|View full text |Cite
|
Sign up to set email alerts
|

Defective trafficking and localization of mutated transferrin receptor 2: implications for type 3 hereditary hemochromatosis

Abstract: Wallace DF, Summerville L, Crampton EM, Subramaniam VN. Defective trafficking and localization of mutated transferrin receptor 2: implications for type 3 hereditary hemochromatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 38 publications
3
23
0
Order By: Relevance
“…In contrast, adult KI mice have normal transferrin saturation and LIC and develop liver iron overload only with aging. Although it has been previously shown that, in overexpressing cells, the mutated Tfr2-M167K ␣ protein is predominantly retained in the endoplasmic reticulum and does not reach the plasma membrane, 25 the phenotype of KI mice indicates that in vivo this variant is functional. Furthermore, KI mice show transient macrocytic anemia during weaning but surprisingly accumulate iron in spleen macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, adult KI mice have normal transferrin saturation and LIC and develop liver iron overload only with aging. Although it has been previously shown that, in overexpressing cells, the mutated Tfr2-M167K ␣ protein is predominantly retained in the endoplasmic reticulum and does not reach the plasma membrane, 25 the phenotype of KI mice indicates that in vivo this variant is functional. Furthermore, KI mice show transient macrocytic anemia during weaning but surprisingly accumulate iron in spleen macrophages.…”
Section: Discussionmentioning
confidence: 97%
“…These two vectors were engineered to contain either amino-or carboxyl-terminal double-myc (DMyc) tags, and their construction is described in Ref. 36.…”
Section: Methodsmentioning
confidence: 99%
“…16 The absence of surface expression of mutant TFR2 would hamper the interaction with diferric transferrin and the activation of the signaling pathway resulting in hepcidin induction. This likely occurs also in the present case in which the lack of exon 4 extensively disrupts the extracellular domain of the full transmembrane protein.…”
Section: © F E R R a T A S T O R T I F O U N D A T I O Nmentioning
confidence: 99%